Critical Thermal Maxima of Bombus impatiens: from Castes to Colonies - Bretzlaff, Tiffany (Université d'Ottawa / University of Ottawa, 2023)
Bumblebees are experiencing declines and range contractions globally that are, in some cases, independent of anthropogenic pesticide- or land-use change, leaving rising global temperatures as the primary driver of such loses. With ambient temperature (Ta) and thermal limitations being a crucial component in these observed declines, I sought to determine the physiological limitations that high Ta imposes on both individuals and colonies of a temperate bumblebee species, Bombus impatiens. Through Chapter 2, I first established the upper thermal tolerance (CTmax) of the species, testing both adults and larvae to determine which of these colony castes are most thermally sensitive to heat. Collective thermoregulation at the colony-level is then important to ensure that the most heat sensitive individuals are protected from changes in optimal nest temperature (Tn). I thus identified the energetic costs associated with colonial thermoregulation and whether large colonies could successfully achieve thermal homeostasis under various Ta. Chronic bouts of heat stress are also of concern as colonies invest time and energy into thermoregulation, especially given that heatwave events are becoming more frequent. In Chapter 3, I examined whether there exists a trade-off between thermoregulation and foraging effort for colonies under chronic heat stress and how various measures of colony success are impacted. Finally, foraging requires individuals to employ flight for the procurement of resources. In Chapter 4, I investigated if the temperate adaptation of an insulative pile layer would hinder flight performance under high Ta by assessing the metabolic rates of adult castes during flight. I found that larvae were more thermally sensitive compared to bumblebee adults, which emphasizes the importance of colonial thermoregulation – a task successful at low Ta. Under heat stress, however, Tn could not be maintained despite elevated energetic investments (Chapter 2). These findings suggest that Ta which exceeds optimal Tn may pose significant challenges to colonies; not only energetically but also to the health of thermally sensitive larvae within. A trade-off between thermoregulation and foraging effort did not emerge for colonies experiencing chronic exposure to high Ta. Instead, only high incidences of thermoregulation were observed which failed to prevent increases in Tn. Furthermore, a greater number of individuals were found to abandon the colony at high Ta, and fewer offspring were produced (Chapter 3). Here, findings suggest that chronic high Ta may pose the greatest risk to the production of thermally sensitive offspring by way of reduced worker population and failed thermoregulation. Finally, the metabolic output during flight at high Ta was not found to be affected by an insulative layer of pile (Chapter 4), indicating that either pile may play a role in limiting other measures of flight performance at high Ta, or that alternate physiological mechanisms may be responsible instead. Together the findings from this thesis broaden the understanding of how a temperate species of bumblebee responds physiologically to high Ta both at the individual and colonial level, providing further evidence on thermal limitations in a changing climate.
Keywords: Bumblebee; Heat tolerance; Thermoregulation; Heat stress; Flight performance; Bumblebee colonies